COVID-19 vaccine acceptance and its associated factors in the Western Pacific RegionResearch in context - Shihui Jin; Leesa Lin; Heidi J. Larson; Alex R. Cook (Elsevier, 2024)
Summary: Background: COVID-19 vaccines effectively reduced the severity of the pandemic, but the mass rollout was challenged by vaccine hesitancy, which was related to heterogenous factors-such as religiosity, mistrust, and a lack of scientific knowledge-around the globe. Distinguishing these potential influencers and quantifying their impacts would help authorities to tailor strategies that boost vaccine confidence and acceptance. Methods: We conducted a large-scale, data-driven analysis on vaccine acceptance and actual uptake in eight Western Pacific countries before (2021) and after (2022) the mass COVID-19 vaccine rollouts. We compared vaccine acceptance or uptake rates between different subpopulations using Bootstrap methods and further constructed a logistic model to investigate the relationship between vaccine endorsement and diverse socio-demographic or trust-related determinants at these two time points. Findings: Substantial between-country differences in vaccine acceptance and uptake were observed across the Western Pacific, with Mongolia, Vietnam, Laos, Cambodia, and Malaysia being more pro-vaccine than the other three countries (Japan, South Korea, and the Philippines). Actual vaccination rates in 2022 were all higher than predicted from the 2021 responses. Influencers for vaccine endorsement were country-specific, but generally, groups susceptible to vaccine hesitancy included females, the less-educated, and those distrusting vaccines or health care providers. Interpretation: Our findings demonstrate the successful translation of vaccine intent to actual uptake with the deployment of COVID-19 vaccination in the Western Pacific. Increasing vaccine confidence and supressing dissemination of misinformation may play an essential role in reducing vaccine hesitancy and ramping up immunisation. Funding: AIR@InnoHK.